Why are executives interested in technology policy?——Research on the mechanism of science and technology policy affecting enterprise innovation - Weiping Liu; Shixin Yang (Journal of Frontier in Economic and Management Research, 2025)
This paper selects the A-share non-financial listed companies in China from 2007 to 2018 as the research object to study the impact of science and technology policy on enterprise innovation and its influence mechanism, and further explore the effectiveness boundary of science and technology policy. The results show that there is a significant positive correlation between science and technology policy and executive compensation; there is a significant positive correlation between technology policy and enterprise innovation; there is a significant positive correlation between science and technology policy and enterprise innovation; executive compensation plays a partial intermediary effect between technology policy and enterprise innovation. Further research on the effectiveness boundary of science and technology policy shows that: first, management power can strengthen the positive correlation between science and technology policy and executive compensation; second, regional factors have a greater impact on the relationship between science and technology policy and enterprise innovation. The ethnic regions and western regions with poor economic development level weaken the positive incentive effect of science and technology policies on enterprise innovation.